Effects of plyometric training in sand or on a rigid surface on physical performance responses and testosterone concentration in football players - Hatem, M. L. (Proximus Journal of Sports Science and Physical Education, 2024)
Background This study aimed to assess the effects of 8 weeks of plyometric training (PT) conducted on sand or a rigid court surface on physical-performance responsesand testosterone concentration in football players.